BS25. Language inhibition and motor response thresholds during extra-operative cortical stimulation mapping. (May 2018) - Aungaroon, Gewalin; Vera, Alonzo; Horn, Paul; Holland, Katherine; Arya, Ravindra
Abstract : Introduction: Electrical cortical stimulation (ECS) is the clinical standard for brain mapping to define the functionally eloquent cortex in patients undergoing pre-surgical evaluation with intracranial electrodes. This study evaluated thresholds for language inhibition and motor response during ECS and their determinants. Methods: A retrospective review of clinical information and extra-operative electrocorticography (ECoG) recordings was performed. The thresholds for functional responses were determined and compared with after-discharge (AD) thresholds. Multivariate models were used to evaluate predictors of functional thresholds. Results: A total of 122 children were included. The mean language threshold was 7.4 ( ± 3.0) mA. 40/47 (85%) of patients with language response during ECS also had ADs. Language thresholds were found to be equal to or higher than AD thresholds in 34/40 (85%) patients. The mean motor threshold was 5.4 ( ± 2.8) mA. 71/85(83.5%) of patients with motor response during ECS also had ADs. Motor thresholds were found to be equal to or higher than AD thresholds in 47/71 (66%) patients. Minimum AD threshold was a significant determinant of minimum language threshold (regression co-efficient 0.446, 95% CI −0.001 to 0.892, p = 0.050) and minimum motor threshold (regression co-efficient 0.664, 95%CI 0.058 to 1.270, p = 0.034). Conclusion: AD threshold was a significant determinant of language and motor thresholds. Most children with functional response during ECS also had ADs, with the functional thresholds being equal to or higher than AD thresholds. These findings underscore a potential pitfall in functional cortex localization with ECS findings and emphasize the need for a functional mapping method with improved neurophysiologic validity, especially in children.